Tanggungjawab Developer atas Keterlambatan Pembangunan terhadap Pembeli dalam Perjanjian Jual Beli Rumah (Studi pada PT X) - Sania Bintang, Nadya Putri; Isnaini, Isnaini (JUNCTO: Jurnal Ilmiah Hukum, 2025)
The purpose of this study is to examine the Developer's Responsibility for delayed construction to buyers in a house sale and purchase agreement (Study on PT X). In this case, it will discuss the principles of contract law, applicable regulations, and legal consequences of delayed house construction by developers to buyers in a house sale and purchase agreement. In the context of a house sale and purchase agreement, buyers can be harmed if there is a delay in construction in the house sale and purchase contract. The developer PT X was involved in a case of delayed housing construction. PT X and the buyer had a promise of a construction completion time in the house sale and purchase agreement. However, PT X failed to complete the construction on time, causing consumers to be harmed. Consumers then sued for compensation because the service was not available. This case shows how important the developer's legal responsibility is in fulfilling the obligations of the agreement and providing legal protection to consumers. The role of the developer is very important to ensure that the construction project is completed on time as stipulated in the contract. The method used is the normative legal research method, with data collection instruments for documentation studies and interviews, while data analysis uses descriptive analysis. The results of this study indicate that PT X has a legal obligation to complete construction according to the agreement on time. Due to the delay, consumers suffer material and immaterial losses. Developers are required to pay for these losses in accordance with the provisions of consumer protection law.